Mesenchymal stem cells and exosomes: A novel therapeutic approach for aging - Dongfeng Lan; Dan Zhang; Xiaofang Dai; Ji Cai; He Zhou; Tao Song; Xianyao Wang; Qinghong Kong; Zhengzhen Tang; Jun Tan; Jidong Zhang (Experimental Gerontology)
Mesenchymal stem cells (MSCs), a vital component of the adult stem cell repertoire, are distinguished by their dual capacity for self-renewal and multilineage differentiation. The therapeutic effects of MSCs are primarily mediated through mechanisms such as homing, paracrine signaling, and cellular differentiation. Exosomes (Exos), a type of extracellular vesicles (EVs) secreted by MSCs via the paracrine pathway, play a pivotal role in conveying the biological functions of MSCs. Accumulating evidence from extensive research underscores the remarkable anti-aging potential of both MSCs and their Exos. This review comprehensively explores the impact of MSCs and their Exos on key hallmarks of aging, including genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, impaired macroautophagy, deregulated nutrient-sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, altered intercellular communication, chronic inflammation, and dysbiosis. Furthermore, this paper highlights emerging strategies and novel approaches for modulating the aging process, offering insights into potential therapeutic interventions.